GutAlive® enables DNA-based microbiome analysis without disrupting the original composition and diversity - Montero, Ignacio; Barrientos, Desirée; Hidalgo-Cantabrana, Claudio; Martínez-Álvarez, Noelia (Frontiers in Microbiology, 2023)
A precise faecal microbiome analysis requires normalized methods for microbiome sampling, transport and manipulation in order to obtain a representative snapshot of the microbial community. GutAlive® is the unique stool collection kit that generates an anaerobic atmosphere enabling oxygen sensitive bacteria to survive, maintaining the original microbiome composition and diversity. In this work we analyze the usability of GutAlive® for DNA-based microbiome analysis and compare its performance with DNA/RNA Shield®. Our results show that GutAlive® enables bacterial viability and DNA integrity overtime, obtaining high-quantity and high-quality DNA to perform microbiome analysis by shotgun metagenomics. Based on taxonomic profiling, functional analysis, phylogeny and metagenome-assembled genomes, GutAlive® displayed greater performance without significant variability over time, showcasing the stabilization of the microbiome preserving the original composition and diversity. In addition, this DNA stabilization is enabled with the bacterial viability on an anaerobic environment, without the need of adding any reagents to the sample. All the above makes GutAlive® an user-friendly kit for self-collection of biological samples, suitable for microbiome analysis, diagnostics, faecal microbiota transplant and bacterial isolation, maintaining the stability and bacterial viability over time, preserving the original composition and diversity of the microbiome